Study the Features and Impact of Myofascial Pain Dysfunction Syndrome on Females - Hanoon, Hind A.; ALsadoon, Asawer Kareem; Naheema, Ghufran L. (American Journal of Biodiversity, 2025)
Myofascial pain syndrome (MPS) is a type of pain that arises from myofascial trigger points in skeletal muscle. The symptoms of MPDS include pain, limited jaw movement, and tenderness in the masticatory muscles. Patients report mild to severe deep aching sensations that are localized or regional. Among the pharmacological therapies are Non - steroidal anti-inflammatory medications, myoreaxent,antidepressants, and anticonvulsants. Patients are also treated with physiotherapy using ultrasound and transcutaneous nerve stimulation (TENS), trigger point dry needling, and occlusal splints (night guards) with local massages using olive oil. Findings: Every treatment approach will reduce MFPD to varying degrees while causing various systemic and local adverse effects. DISCUSSION: Accurate diagnosis and appropriate treatment based on knowledge of the disorder's genesis are essential for the effective care of individuals with MPDS syndrome.